An observational study to evaluate the effect of different epidural analgesia regimens on dynamic pain scores in patients receiving epidural analgesia for postoperative pain relief after elective gynecological surgery - Manpreet Singh; Ranju Singh; Aruna Jain (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: The primary measure of efficacy of any analgesic regimen is pain relief, but it is important to measure dynamic pain relief rather than pain relief at rest. Epidural analgesia is an effective technique for postoperative analgesia. The drug combinations given therein (local anesthetics with adjuvants such as opioids/alpha-2 agonists), however, remain a personal choice. The aim of this study was to evaluate dynamic pain scores in patients receiving different epidural analgesia regimens for postoperative pain relief after elective gynecological surgery used in our institution. Material and Methods: One hundred eighty-seven patients enrolled in this study received postoperatively either bupivacaine 0.125% + morphine 0.1 mg/mL (group BM) or bupivacaine 0.125% + fentanyl 2 μg/mL (group BF) or bupivacaine 0.125% + clonidine 1 μg/mL (group C1) or bupivacaine 0.125% + clonidine 2 μg/mL (group C2) by continuous epidural infusion @ 5 mL/h. Differences in dynamic pain scores (on coughing and mobilization), pain scores at rest, sensory and motor blockade, sedation scores, dry mouth, pruritus, nausea, and vomiting were recorded. Also duration of postoperative analgesia, epidural top-ups, requirement of rescue analgesic, and patient satisfaction were determined. All observations were carried out at 1, 2, 4, 8, and 12 h after surgery and then at 8 am, 12 noon, 4 pm, 8 pm on subsequent postoperative day till removal of epidural catheter (after 96 h). Results: There was no difference in demographic or hemodynamic profile among the four groups (P > 0.05). There was no statistically significant difference in pain scores at rest among the four groups but dynamic pain scores were found to be better in group C2 as compared to group BM, BF, and C1 at most of the time intervals although not statistically significant (P > 0.05). Requirement of rescue analgesics was lower in group BM and group C2 as compared to group BF and C1 (P < 0.01). Incidence of pruritus was 43.5% in group BM and 19% in group BF, while no patients in group C1 or C2 had pruritus. Mean postoperative nausea and vomiting (PONV) scores were higher in group BM and group BF as compared to group C1 and C2 (P < 0.001). Mean sedation scores were comparable in all four groups. Incidence of dry mouth was 22% in group C2 as compared to 11% in group C1, while no patients in group BM or BF had dry mouth. Patients in group C2 were more satisfied as compared to other three groups. Conclusions: Combination of clonidine 2 μg/mL to 0.125% bupivacaine @ 5 mL/h in combined spinal epidural provides better postoperative analgesia as compared to combination of bupivacaine with opioids with greater patient satisfaction and significantly reduced side effects.